2014
DOI: 10.1177/1535370214554532
|View full text |Cite
|
Sign up to set email alerts
|

Role of xenogenous bovine platelet gel embedded within collagen implant on tendon healing: an in vitro and in vivo study

Abstract: Surgical reconstruction of large Achilles tendon defects is demanding. Platelet concentrates may be useful to favor healing in such conditions. The characteristics of bovine platelet-gel embedded within a collagen-implant were determined in vitro, and its healing efficacy was examined in a large Achilles tendon defect in rabbits. Two cm of the left Achilles tendon of 60 rabbits were excised, and the animals were randomly assigned to control (no implant), collagen-implant, or bovine-platelet-gel-collagen-implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…42,49,88 Platelet rich plasma (PRP) and its other forms (gel and glue) can be obtained from patients' anticoagulant peripheral blood by one or two step centrifugation. 107,119,[121][122][123] PRPs are different from each other based on their platelet concentration which is 1.5 to 10 times greater than the physiologic plasma. In addition, they are different based on their source (auto-, allo-, and xenograft), and also presence/absence and concentration of white blood cells.…”
Section: Co-administration Of Healing Promotive Factors and Stem Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…42,49,88 Platelet rich plasma (PRP) and its other forms (gel and glue) can be obtained from patients' anticoagulant peripheral blood by one or two step centrifugation. 107,119,[121][122][123] PRPs are different from each other based on their platelet concentration which is 1.5 to 10 times greater than the physiologic plasma. In addition, they are different based on their source (auto-, allo-, and xenograft), and also presence/absence and concentration of white blood cells.…”
Section: Co-administration Of Healing Promotive Factors and Stem Cellmentioning
confidence: 99%
“…The most important growth factor of platelet concentrates is PDGF which is responsible for several osteoinductive and osteoconductive events. 4,119,121 Therefore, combination of PRP or PDGF with Simvastatin is an interesting option in inducing osteogenesis.…”
Section: Co-administration Of Healing Promotive Factors and Stem Cellmentioning
confidence: 99%
“…Collagen is a favorite material for tendon regeneration since it is the major ECM component in tendons. Several studies have demonstrated the applicability of different forms of collagen in tendon healing [25][26][27][28]. Collagen has well-documented structural, physical, chemical and immunological properties including high availability, easy purification from living organisms, low antigenicity, non-or low-cytotoxicity, good hemostatic and cell-binding properties as well as biological plasticity [10,29].…”
Section: Collagen and Tendon Healingmentioning
confidence: 99%
“…Two main issues with collagen include the low strength provided by collagen and its high degradation that is not desired for an ideal delivery system or carrier [34]. To overcome these issues and having a sustained release of growth factors, some researchers have fabricated the delivery systems to express lower degradation rate so that the scaffold can retain the growth factors for a long time at the implantation site [27,28,34]. Some researchers have cross-linked the collagen fibers with other biomaterials to enhance their biomechanical properties [35,36].…”
Section: Collagen and Tendon Healingmentioning
confidence: 99%
See 1 more Smart Citation